On the borderline between poetry and historiography. The culture of the Balkan ġāzī as seen through the eyes of 15th-century Ottoman chroniclers and poets - Dobosz, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2025)
Among the preserved works of 15th-century Ottoman historiography, there are several examples of poems that are related to the idea of conducting a ġazā. Analysis of these works leads to conclusions that partly confirm previous findings in the literature, but also to new insights. The ġāzī community encompassed representatives of various social groups who interpreted this concept differently and had different goals related to it. Muslim scholars tried to impose certain rules based on moral principles. Their approach also assumed being a link between the borderland and the center. The palace aimed to lead the conquests and subjugate the border warriors. Among the latter, there were elements of culture whose tradition can be traced back to the first centuries of Islam. Something important for them, apart from enrichment, was the bond with the conquered land, which was not only a new part of the domain of Islam, but also their small homeland.